Febrile neutropenia in childhood leukemia: Manado experience 1997 - 2006 - Stefanus Gunawan; Novie Homenta Rampengan; Max Frans Joseph Mantik; Tonny Homenta Rampengan (Paediatrica Indonesiana, 2009)
Background Febrile neutropenia (FNP) is a common complicationof therapy among children with cancer. It is one of the causes ofsignificant morbidity and mortality in children and young adultstreated for cancer. With aggressive management of FNP, theoutcome of episodes in children has improved dramatically.Objective To determine factors associated with FNP, to assess how varied the current management, and to evaluate the outcome of FNP in childhood leukemia in Manado over the last 10 years.Methods Data from medical records was collected retrospectivelyfrom January 1997 to December 2006. Variables studied were: age, sex, nutritional status, sosio-economic status, type of leukemia, degree of fever, ANC at fever, phase of chemotherapy, antibiotic used, episodes ofFNP and the outcome of patients.Results Twenty of ninety one patients were studied. The mortality rate was crucial i.e., 11 of20, it was higher in boys than that in girls. Most children have severe to very severe neutropenia and more than half died (7 /13). Seven out of 12 malnourished patients died. Sixteen children are suffered from acute lymphoblastic leukemia (ALL). The outcome of high risk (HR) patients was worse than that of standard risk (SR). FNP occurred along the phase of chemotherapy. None of the factors studied showed significant difference. The choice of antibiotics is varied.Conclusion The outcome of FNP in our institution is grave.There is a need to evaluate application and compliance to thestandard guidelines.